THE IMPROVEMENT OF THE COMPENSATION PROCEDURE IN MONETARY FORM FOR LOST OR DAMAGED FREIGHT WAGONS OF OTHER STATES - Gnennyi, O. M. (Science and Transport Progress, 2009)
It is found that the cost of lost (damaged) wagons determined in accordance with the operating order of indemnity of losses differs considerably from the market cost. This difference is related to a discrepancy of normative prices on new wagons to the prices of manufacturers as well as to a gap of used method of account of wagon deterioration to the relation between the cost and the time of wagon operation, which is at the market. At the choice of money form of indemnity of losses, it is suggested to determine the wagon cost by independent (expert) estimate or the set norms at the discretion of railway administration-owner. In so doing, to change the method of determination of wagon deterioration from a rectilinear one on a method of decreasing rest. In addition, the periodic update of normative prices on new wagons should be provided.